DINAMIKA LSM DALAM LEGISLASI KEBIJAKAN RESPONSIF GENDER: STUDI KASUS LSM DAMAR DI KOTA BANDAR LAMPUNG - Syamsul Ma’arif (Yogyakarta State University, 2017)
This study was aimed to explain the social role that had been carried out, capacity building that had been done, and the capacity of the DAMAR NGO in fighting for the issuance of gender responsive public policies especially related to the fulfillment of women's basic rights. The results showed that the NGO DAMAR was successful in actualizing the social role of NGOs which included: supervision of the Government, policy advocacy and empowerment, and civic education even on a limited scale. Capacity building had been carried out by NGO DAMAR at various levels, both at the system level, institutional level, and individual level, so that making DAMAR NGOs have independence and self-sufficiency. But he had not been able to realize self-sufficiency through the establishment of productive business units. For this reason, NGO DAMAR was necessary to develop independent funding sources by transferring funding sources from abroad to local funding sources through the establishment of productive business units.